UJI BEBAN PADA STRUKTUR BANGUNAN CAGAR BUDAYA JEMBATAN LOJI KOTA PEKALONGAN - Sabdono, Parang (Universitas Sains dan Teknologi Komputer, 2023)
The Loji Bridge in Pekalongan City is a cultural heritage building that was built in 1880, during the Dutch East Indies colonial period. The Loji Bridge is more than 150 years old and is still standing and is only used for bicycle and motorbike traffic. When it was built, it was an important bridge because it was a bridge on the north coast road. Until now, this has been the way of the economy. The condition of the bridge is currently unknown as to its structural feasibility. The Pekalongan city government will revitalize the bridge left over from the Dutch era so that it can be used again. If it is not possible for traffic to be used, it will be used as a place for MSME activities. So in the city of Pekalongan there are interesting places to attract visitors as culinary tourism spots and others.To determine the suitability of the bridge structure with a span of 50 meters, testing needs to be carried out. The test carried out is a load test. Why is a loading test carried out because there is no bridge building data, superstructure data or substructure/foundation data. So with a loading test you can immediately determine the amount of load the bridge can safely withstand.The loading method uses water loads, namely by creating a loading pool. The load is adjusted to the planned traffic load / live load. The equipment installed and recorded during the test is to determine and monitor the bridge settlement, either in the pillars or beams. Monitoring is carried out to maintain deflection / settlement. So that the decrease / deflection that occurs during testing is still within safe limits.The equipment used to monitor and record deflection is a Linear Variable Displacement Transducer (LVDT) which is connected to a data logger and computer. The LVDT is placed on wooden stakes / poles stuck into the river bed, so that the readings decrease relative to the river bed.Loji Bridge with a span of 50 meters consists of 4 pillars and 2 abutments. Upper structure with asphalt pavement, wooden plank floor. The abutments use river stone pairs and the pillars use 7 solid pipes with a diameter of 12 cm. Later, it is planned to replace the wooden floor with a reinforced concrete slab floor on the bridge.